Improving Religious Literacy Through Islamic Religious Education Course Based On The Flipped Classroom - Suci Nurpratiwi; Muhamad Ridwan Effendi; Amaliyah Amaliyah (Postgraduate Program Magister Pendidikan Agama Islam, 2021)
Religious literacy is essential because understanding religious doctrine is about the normative principle and how religion applies in a social context. Religious literacy can develop through the learning process. This study analyzes student religious literacy by learning Islamic Religious Education (IRE) based on the flipped classroom. The research method used is classroom action research through two cycles. The research subjects were students who took the general course of Islamic Religious Education. The results showed that applying flipped classrooms in Islamic Religious Education learning could increase student diversity in belief, practice dimensions, knowledge dimensions, and implementation dimensions. The implementation of Islamic learning based on flipped classroom can also improve student learning activities. Students pay attention to learning carefully, actively participate in discussions, actively ask questions, provide opinions, and perform assigned tasks. Besides that, the implementation of a flipped classroom can also improve student learning outcomes.Literasi keberagamaan penting dimiliki karena memahami ajaran agama bukan hanya sebatas pada doktrin normatifnya saja, melainkan juga pada bagaimana agama diterapkan dalam konteks sosial. Literasi keberagamaan dapat dikembangkan melalui proses pembelajaran. Penelitian ini bertujuan untuk menganalisis peningkatan literasi keberagamaan mahasiswa melalui pembelajaran Pendidikan Agama Islam berbasis flipped classroom. Metode penelitian yang digunakan adalah classroom action research dengan melalui dua siklus. Subyek penelitian adalah mahasiswa yang mengambil mata kuliah umum Pendidikan Agama Islam. Hasil penelitian menunjukkan bahwa penerapan flipped classroom dalam pembelajaran Pendidikan Agama Islam dapat meningkatkan literasi keberagamaan mahasiswa pada dimensi keyakinan, dimensi praktik, dimensi pengetahuan, dan dimensi pengamalan. Penerapan pembelajaran Pendidikan Agama Islam berbasis flipped classroom juga dapat meningkatkan aktivitas pembelajaran mahasiswa, mahasiswa memperhatikan pembelajaran secara seksama, aktif berpartisipasi dalam diskusi, aktif mengajukan pertanyaan dan memberikan pendapat, serta mengerjakan tugas-tugas yang telah diberikan. Di samping itu, penerapan flipped classroom juga dapat meningkatkan hasil belajar mahasiswa.